Macular function assessed by microperimetry in patients with enhanced S-cone syndrome. - Sohn, E; Chen, F; Rubin, G; Moore, A; Webster, A; Maclaren, R (2010)
PURPOSE: Enhanced S-cone syndrome (ESCS), also known as Goldmann-Favre syndrome, is a progressive retinal degeneration that frequently presents with night blindness and nummular pigment clumping around the vascular arcades and is caused by recessive mutations in the photoreceptor-specific NR2E3 transcription factor. A unique feature of this disease is the development of retinoschisis of the macula. This study used fine anatomic and functional assessments within this region to determine whether the loss of retinal function was due to progressive schisis or a primary photoreceptor loss, similar to other rod-cone dystrophies. DESIGN: Cross-sectional, prospective study. PARTICIPANTS: Nine probands (n=18 eyes) and 3 controls (n=6 eyes) were studied at Moorfields Eye Hospital in London, United Kingdom. METHODS: Histories were obtained and visual acuity was measured using Early Treatment Diabetic Retinopathy Study protocol. Autofluorescence (AF), fundus photography, and spectral domain optical coherence tomography (OCT) imaging were co-registered to detailed microperimetry (Nidek MP1; NAVIS software version 1.7.2; Nidek Technologies, Padova, Italy) data for statistical analysis. MAIN OUTCOME MEASURES: Retinal sensitivity (decibels) in a customized test grid of the macula; retinal structure assessed with OCT and AF. RESULTS: Patients were divided into 3 cohorts roughly based on life span and documentation of schisis: (1) no schisis, childhood; (2) macular schisis, young adults; (3) resolved schisis, older adults. Retinal sensitivity was significantly attenuated in those with schisis and did not recover in those whose schisis had resolved despite retinal thickness comparable to that of controls. All probands exhibited loss of AF peripherally (and corresponding loss of retinal sensitivity), but there was relative preservation of AF within the macula. CONCLUSIONS: Development of macular retinoschisis in ESCS is an important feature of the disease and contributes to attenuated retinal sensitivity that persists after resolution of retinoschisis. The central macula appears to be compromised more by foveoschisis than photoreceptor loss. In contrast, the peripheral retina (ordinarily a rod-rich region) is affected early in the disease process and degenerates rapidly because of photoreceptor loss. Thus, 2 distinct mechanisms of retinal degeneration may exist in ESCS, corresponding to regions of the retina that may experience either normal or abnormal photoreceptor development.